2018
DOI: 10.1073/pnas.1718891115
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the neurofunctional bases of intentional action

Abstract: Here we challenge and present evidence that expands the ,, and anatomical model of intentional action, which states that internally driven decisions about the content and timing of our actions and about whether to act at all depend on separable neural systems, anatomically segregated along the medial wall of the frontal lobe. In our fMRI event-related paradigm, subjects acted following conditional cues or following their intentions. The content of the actions, their timing, or their very occurrence were the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 37 publications
(36 reference statements)
4
46
0
Order By: Relevance
“…Nevertheless, in line with the idea that a medial frontal pathway is of particular importance for endogenous action selection (Passingham 1987;Brass and Haggard 2008;Soon et al 2008;Fried et al 2017;Zapparoli et al 2018), we found that MFC was the only area that represented endogenous components of both initial decisions and later decision reversals. More specifically, MFC encoded CoM in participants who more strongly considered endogenous information, but not in those who exclusively relied on external cues, i.e., target distance.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, in line with the idea that a medial frontal pathway is of particular importance for endogenous action selection (Passingham 1987;Brass and Haggard 2008;Soon et al 2008;Fried et al 2017;Zapparoli et al 2018), we found that MFC was the only area that represented endogenous components of both initial decisions and later decision reversals. More specifically, MFC encoded CoM in participants who more strongly considered endogenous information, but not in those who exclusively relied on external cues, i.e., target distance.…”
Section: Discussionsupporting
confidence: 87%
“…First, participants were required to generate an arbitrary endogenous decision for a visually presented face or house stimulus without any choice outcome being associated with rewards at this stage. We derived ROIs from previous studies and confirmed that initial voluntary decisions were encoded in MFC, precuneus, dlPFC and AG (Brass and Haggard 2008;Soon et al 2008;Bode et al 2011;Krieghoff et al 2011;Bode et al 2013;Soon et al 2013;Zapparoli et al 2018). Additionally, decisions could be decoded from visual cortex, presumably due to visual fixation of the chosen image, and attention to visual features of the chosen image (Krajbich et al 2010;Rens et al 2018;Voigt et al 2019).…”
Section: Discussionsupporting
confidence: 69%
“…There is a rich body of fMRI literature showing how internally and externally triggered actions are sub-served by partially different neural patterns. Studies comparing conditions in which subjects have to press a button at a moment of their own choice (internally triggered actions) to conditions in which subjects are prompted to press the button by a visual or acoustic cue (externally triggered actions) report greater activation of the SMA/preSMA associated with internally triggered actions (see Zapparoli et al, 2017Zapparoli et al, , 2018. On the contrary, externally triggered actions seem to be more associated with the activity of visual or auditory cortices, depending on the type of external trigger signal (Cunnington et al, 2002;Jenkins et al, 2000).…”
Section: Accepted Articlementioning
confidence: 99%
“…The notion of a context-invariant encoding of task information in a single brain region has long been challenged: It is known that different variables of tasks might be encoded in different regions across the cortex, supporting a distributed model of task encoding (Jahanshahi, 1998), which is in line with the Multiple Demand Network framework (Fedorenko, Duncan, & Kanwisher, 2013). Furthermore, when preparing actions the information about ‘what’ will be performed and ‘when’ it will be performed is encoded in dissociable brain regions (Soon, Brass, Heinze, & Haynes, 2008; Zapparoli et al, 2018), in line with Brass and Haggard’s (2008) distinction of the ‘what’, ‘when’ and ‘whether’ subprocesses of intentions (see also Krieghoff, Brass, Prinz, & Waszak, 2009; Momennejad & Haynes, 2012). Our results can be interpreted as an extension of this deviation from a singular process, or locus, by showing that the ‘what’ is not a discrete process either, but a process that depends on the context in which the action decision is made.…”
Section: Discussionmentioning
confidence: 55%